THE ROLE OF WORK PROTECTION PROGRAMS, REWARD SYSTEMS, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE - Prastyo, Edo; Martaleni, Martaleni; Ariyani, Fitria; Arumsari, Yuni Kusuma; Astuti, Rini (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
Advances in technology and increasingly intense industrial competition require companies to continuously improve their management practices. In addition to ongoing innovation and efficiency, the management of human resources demands serious and competitive attention. One of the main challenges faced by companies in the logistics and manufacturing sectors is creating a work environment that can support employees in achieving optimal performance. This study aims to analyze the influence of Work Protection Programs, Reward Systems, and Job Satisfaction on Employee Performance. The research was designed using a quantitative approach, with data collected through a five-point Likert scale questionnaire distributed to 100 employees systematically selected from a total population of 254. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26.0, along with classical assumption testing. The results indicate that work protection, reward systems, and job satisfaction simultaneously have a significant effect on employee performance. Partially, job satisfaction has the most dominant and significant influence, followed by work protection programs and reward systems. These findings highlight that enhancing job satisfaction, along with strengthening protection and reward systems for employees, are crucial strategies to improve performance. The practical implication of this study suggests that integrated human resource policies oriented toward employee well-being are highly relevant to be implemented in the logistics and manufacturing sectors to foster organizational productivity and effectiveness. Keywords: work protection, reward system, job satisfaction, employee performance